Mycoflora Associated with Barely Grains (Hordeum vulgare L.) in the Eastern Parts of Libya - Abdullah, Marei (Scientific Journal for Faculty of Science-Sirte University, 2022)
During the harvest season (2019-2020), local variety of barley seeds (Hordeum vulgare L.) were collected from three different locations, Almerj, Gerdina, and Sultan; situated in the eastern part of Libya. The present experiment was performed to identify, and compare natural mycoflora associated with barley seeds among these locations, also to evaluate sodium hypochlorite’s application, as seed disinfectants against fungal contaminators. Barley seeds were surface disinfected with a 4% sodium hypochlorite for two minutes or washed only with deionized water (control) before plating on potato dextrose agar (PDA) medium. The following parameters were recorded and calculated: seed survival (G %), fungal frequency (F), isolation frequency (IF) and fungal relative abundance (RD). Four fungal species were identified as Aspergillus niger van Tiegh, A. flavus Link (ascomycetes), Rhizopus stolonifera (Ehrenb. :Fr.) Vuill (zygomycetes), and Bipolaris australiensis (Bugnicourt) (ascomycetes). The most predominant recovered species was A. niger followed by B. australiensis, R. stolonifera, and A. flavus, (18.5%), (9.67%) (2.84%), (4.65%), respectively. Results also showed Sultan had the highest seed germination, followed by Almerj and Gerdina, 64.5 %, 44.5%, and 20.5 %, respectively. Moreover, seed’s pretreatment with sodium hypochlorite and seed’s origin had no significant effect on frequency and relative abundance of fungi.